THE SWISS ON THE CROSSROADS OF EURASIA: A MICRO SUBJECT MATTER OF URBAN STUDIES FROM THE PERSPECTIVE OF UKRAINE’S NATIONAL HISTORY (City: History, Culture, Society, 2023)
Even though urban studies typically focus on microhistory, a sound macrohistorical perspective is essential. In terms of urbanization in Ukraine, this is the history of Ukraine. Given that the proclamation of an independent Ukrainian state in 1991 altered the subject of Ukrainian history, the article draws attention to the fact that Ukrainian historiography still requires a comprehensive revision of Ukrainian history. The sovereign Ukraine established a new subject of human history distinct from the Ukrainian people. It united the diverse population of the former Soviet province into one nation, and the Ukrainian people became the custodians of its sovereignty and cultural identity. Before independence, the only subject for Ukrainian history was the Ukrainian people, whose parameters were fluid. The new subject of Ukrainian history is the past inhabitants of the sovereign Ukrainian state’s territory. The new topic has significantly expanded spatial, temporal, and cultural dimensions that are nonetheless fixed. This article provides a view of Ukrainian history defined by this specific topic and evaluates the role of Swiss immigrants to Ukraine in the late nineteenth and early twentieth centuries from this perspective. Long ago, Ukraine arose at a thriving crossroads of Eurasia, where three distinct civilizations coexisted. The Steppe belt has been inhabited by pastoral nomads since prehistoric times. The northern 240 coast of the Black Sea was home to colonies, provinces, and states founded by Mediterranean maritime nations interested in trade with nomads. The forest region, where sedentary Slavs resided, entered history when it became the center of the Rus’ state. The Mongol conquests of the thirteenth century initially incorporated Rus’ and the coastal zone into the political system of the Eurasian Steppe. However, the decline of the Mongol Empire led to the military expansion of its sedentary subjects, followed by agricultural colonization that irreversibly transformed the steppe into the sown. The expansion of Lithuania and Poland, which eventually merged into a single Commonwealth, was greatly accelerated by Western Europe, in particular because it demanded provisions, possessed tools, such as the heavy plough, suitable for farming in the Steppe, and firearms that ensured military superiority over the steppe cavalry. The Ukrainian nation emerged within the Polish-Lithuanian Commonwealth and, as a key player in this process, was able to spread across the territories of all three zones. As prominent agents of industrialization and westernization, the Swiss entrepreneurs who settled in Ukraine between the 19th and early 20th centuries earn a place of honor in Ukrainian history.
Keywords: subject of history; civilization; agricultural colonization; Ukraine; Swiss; entrepreneur